Effects of a football competition based on the Brave League on fair play, goal orientation, effort and pressure-tension on primary school students - Lis-Velado, P.; Carriedo, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
This research analyzed the Brave League (2015) effects on the goal orientation, the fair play, the effort and the pressure-tension on 92 pupils from two state schools (control group: n = 45 and experimental group: n = 47) with an age average of 10.38 years (SD = 0.55). The Intervention program was applied to both groups in 3 sessions of one hour; the control group created an indoor football league, whereas the experimental group continued to elaborate a competitive system based on the Brave League (2015) format, where the conducts of fair play establish the order in the classification. Several contrast tests were taken of the subject average, which results showed that the trial group increased the orientation towards the task) and the perceived effort. These results infer that the competitive formats like the proposed could affect positively the orientation towards the task and the effort throughout the sports competitions.